AXBOROT TEXNOLOGIYALARINING BIOLOGIYA FANLARIGA TA'SIRI (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This study aims to examine the impact of information technology on the biological sciences. Descriptive library-based studies have shown that information technology has had the following three effects in the biological sciences: IT will revolutionize the distance sciences. Later, the advent of computer and information technology has made such significant changes in all aspects of life that its importance cannot be described. Biological sciences are no exception to the benefits of IT. IT leads to significant improvement in biological simulation and modeling; and last but not least, Information Technology demonstrates excellence in laboratory research.